2006
DOI: 10.1525/ac.2006.17.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Ostensibly Shamanic Journeying Imagery in Naïve Participants II: Phenomenological Mapping and Modified Affect Bridge

Abstract: This study develops the methodological framework advanced in Rock, Baynes, and Casey's (2005) experimental study of ostensibly shamanic journeying imagery in naïve participants. Specifically, the present study experimentally investigates the impact of the word landscape, featured in Harner's (1990) shamanic journeying to the Lower World instructions, on the number of landscape‐related images reported; examines the origins of ostensibly shamanic journeying images; and maps the phenomenological state effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 16 publications
2
27
0
Order By: Relevance
“…Although very few studies have investigated this phenomenon systematically, participants exposed to repetitive drumming while completing an imagery task reported significantly different subjective experiences in comparison to participants who completed the imagery task without exposure to drumming [61]. Furthermore, differences between subjective experiences related to shamanic instructions and other instructions, such as sitting quietly, were previously reported by Rock [12], [13]. In a similar vein, Shapiro and Lehrer [62] found that participants given autogenic training (which has some similarities with shamanic journeying) reported more sensations of warmth and heaviness in the limbs than participants in a progressive relaxation group.…”
Section: Discussionmentioning
confidence: 99%
“…Although very few studies have investigated this phenomenon systematically, participants exposed to repetitive drumming while completing an imagery task reported significantly different subjective experiences in comparison to participants who completed the imagery task without exposure to drumming [61]. Furthermore, differences between subjective experiences related to shamanic instructions and other instructions, such as sitting quietly, were previously reported by Rock [12], [13]. In a similar vein, Shapiro and Lehrer [62] found that participants given autogenic training (which has some similarities with shamanic journeying) reported more sensations of warmth and heaviness in the limbs than participants in a progressive relaxation group.…”
Section: Discussionmentioning
confidence: 99%
“…The results of Rock, Casey, and Baynes (2006) and facilitated the development of a tentative fourfold ostensibly shamanic journeying imagery origin typology consisting of autobiographical, symbolic, transpersonal and indeterminate sources. An ostensibly shamanic journeying image may be categorized as autobiographical if it appears to be the derivative of an autobiographical memory, that is, a "memory for events that have occurred in one's life" (Reber & Reber, 2001, p. 423).…”
Section: Previous Experimental Researchmentioning
confidence: 96%
“…The Modified Affect Bridge was developed as one potential partial solution to 2; it was not designed to facilitate unrestricted access to one's unconscious material, but rather to facilitate ordinary remembering among ordinary participants in a non-clinical context. The Modified Affect Bridge was first applied in an experimental context by Rock, Casey and Baynes (2006) and, subsequently, . Rock, Casey, and Baynes (2006) reported that ostensibly shamanic journey images encountered by naïve participants journeying to the lower world with the aid of monotonous drumming at 8 beats-per-second for 15 minutes were just as likely to be derived from autobiographical memories as spontaneous visual mental images reported by naïve participants assigned to the control condition of sitting quietly with eyes open for 15 minutes.…”
Section: Previous Experimental Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…(p. 80) It was early pointed out by Walsh (1989) that scientific research on drumming was rather neglected and that such studies were needed. Since then several studies have been performed, evaluating the phenomenological effects and different aspects of monotonous drumming such as change in mood and visual imagery, as well as comparisons with other induction techniques or instructions Rock, Abbott, Childargushi, & Kiehne, 2008;Rock, Abbott, & Kambouropoulos;2008;Rock, Baynes, & Casey, 2005;Rock, Casey, & Baynes, 2006;Rock, Wilson, Johnson, & Levesque, 2008;Woodside, Kumar, & Pekala, 1997). In the study by a thorough analysis of phenomenological contents during rhythmic drumming (as well as for other induction techniques and control condition) was performed.…”
Section: Kjellgren and Erikssonmentioning
confidence: 99%